Structural Control of Fully Condensed Polysilsesquioxanes: Ladderlike vs Cage Structured Polyphenylsilsesquioxanes - Choi, Seung-Sock; Lee, Albert S.; Hwang, Seung Sang; Baek, Kyung-Youl (AMER CHEMICAL SOC, 2015)
Through fine-tuning of the myriad of reaction conditions for an aqueous base-catalyzed hydrolysis-polycondensation reaction, a facile synthesis of structurally controlled polyphenylsilsesquioxanes was developed. Mechanism and kinetic studies indicated that the condensation reaction proceeded through a T-1 structured dimer, which was quantitatively and in situ formed through mild hydrolysis of a phenyltrimethoxysilane (PTMS) monomer, to give either the cage-structured polyhedral oligomeric silsesquioxanes (POSS) or the corresponding ladderlike silsesquioxane (LPSQ) with excellent yields. Ladderlike and FOSS materials were selectively achieved at higher and lower initial concentrations of PTMS, respectively, and an in-depth spectroscopic analysis of both compounds clearly revealed their structural differences with different molecular weights.
Keywords: SILSESQUIOXANES; HYDROLYSIS; SCATTERING; KINETICS; POSS; MECHANISM